Noise : A Flaw in Human Judgment - Kahneman, Daniel; Sibony, Olivier and Sunstein, Cass R. (London William Collins, 2021)
From the world-leaders in strategic thinking and the multi-million copy bestselling authors of Thinking Fast and Slow and Nudge, the next big book to change the way you think. Wherever there is human judgment, there is noise. Imagine that two doctors in the same city give different diagnoses to identical patients - or that two judges in the same court give different sentences to people who have committed matching crimes. Now imagine that the same doctor and the same judge make different decisions depending on whether it is morning or afternoon, or Monday rather than Wednesday, or they haven't yet had lunch. These are examples of noise: variability in judgments that should be identical. In Noise, Daniel Kahneman, Olivier Sibony and Cass R. Sunstein show how noise produces errors in many fields, including in medicine, law, public health, economic forecasting, forensic science, child protection, creative strategy, performance review and hiring. And although noise can be found wherever people are making judgments and decisions, individuals and organizations alike commonly ignore its impact, at great cost. Packed with new ideas, and drawing on the same kind of sharp analysis and breadth of case study that made Thinking, Fast and Slow and Nudge international bestsellers, Noise explains how and why humans are so susceptible to noise and bias in decision-making. We all make bad judgments more than we think. With a few simple remedies, this groundbreaking book explores what we can do to make better ones.
Include Notes and Index
Keywords: Decision making -- Reasoning (Psychology) -- Judgment